2019
DOI: 10.1111/geb.12910
|View full text |Cite
|
Sign up to set email alerts
|

Functional biogeography of dietary strategies in birds

Abstract: Aim Diet is key to understanding resource use by species, their relationships with their environment and biotic interactions. We aimed to identify the major strategies that shape the diet space of birds and to investigate their spatial distributions in association with biogeographical, bioclimatic and anthropogenic drivers. Location Global. Time period Current. Major taxa studied Birds. Methods We analysed score‐based assessments of eight diet categories for 8,937 out of 10,964 extant bird species. We construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 91 publications
2
18
0
Order By: Relevance
“…Our findings extend this result as we find that the portion of the functional space filled by ecologically rare species does not overlap much that filled by common species, highlighting a functional complementarity, instead of redundancy, between ecologically rare and common species 34 for both mammals and birds. In particular, we show that specific sets of traits were over-contributing to ecological rarity, echoing the results of Barnagaud et al 25 who found that nectarivory, carnivory, and piscivory are rare diets in birds. A significant proportion of ecologically rare mammals and birds are indeed nectarivores or frugivores.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings extend this result as we find that the portion of the functional space filled by ecologically rare species does not overlap much that filled by common species, highlighting a functional complementarity, instead of redundancy, between ecologically rare and common species 34 for both mammals and birds. In particular, we show that specific sets of traits were over-contributing to ecological rarity, echoing the results of Barnagaud et al 25 who found that nectarivory, carnivory, and piscivory are rare diets in birds. A significant proportion of ecologically rare mammals and birds are indeed nectarivores or frugivores.…”
Section: Discussionsupporting
confidence: 89%
“…To that end, worldwide data on Eltonian traits, including the characterization of diet and foraging activity, are relevant candidate features 22 . Global analyses on mammals and birds 20 indeed led to interesting findings about the shape of the functional space of these taxa and about the global distribution of their functional diversity, notably identifying hotspots of functional redundancy [23][24][25][26] . They also highlighted a spatial mismatch between protected areas and taxonomic, phylogenetic, and functional diversity worldwide 27 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ants, ladybirds) are much more abundant at lower latitudes, resulting in a higher selection pressure toward the equator (Roslin et al, 2017). Second, bird communities are more influenced by forest habitat composition at lower latitudes, and more by food availability at higher latitudes (Charbonnier et al, 2016) where the diet variability is lower (Barnagaud et al, 2019), suggesting a stronger effect of local habitat features (e.g. resource availability and habitat suitability) than climatic gradients.…”
Section: Discussionmentioning
confidence: 99%
“…Deviations of functional from phylogenetic structure are likely to occur in birds because avian traits show pervasive convergent evolution (Pigot et al ., 2020), with several morphological trait combinations (Pigot et al ., 2020) and dietary characteristics (Kissling et al ., 2012) having multiple origins within the clade. Dietary traits also show differential associations with phylogenetic structure (Barnagaud et al ., 2019), with nectarivory, frugivory and insectivory being associated with phylogenetic overdispersion, while carnivory being phylogenetically clustered (Barnagaud et al ., 2014), although it is unknown whether these traits show similar relationships with functional structure. Evaluating the association between functional and phylogenetic structure on a global scale, and potential factors in its variation, can help assess their surrogacy for basic and applied questions and hint at ecological and evolutionary causes of assemblage composition (Devictor et al ., 2010; Graham et al ., 2012; Gerhold et al ., 2015; Mazel et al ., 2018, but see Mayfield and Levine, 2010; Cadotte and Tucker, 2017).…”
Section: Introductionmentioning
confidence: 99%